Body mass index as the most influential factor of high-sensitivity C-reactive protein in non-diabetic adults - Mulyamin, Winda; Kurniawan, Liong Boy; Adnan, Endy; Widaningsih, Yuyun; Idris, Irfan; Santoso, Arif; Yustisia, Ika (Faculty of Medicine, Universitas Trisakti, 2021)
BACKGROUNDHigh-sensitivity C-reactive protein (hsCRP) has been widely accepted as a predictor of future cardiovascular risk that reflects a microinflammatory state. Obesity linked to microinflammation increases the prevalence of metabolic disorders and cardiovascular diseases. This study aimed to determine the association between several obesity indices namely body mass index (BMI), waist circumference (WC), body fat percentage (fat), and visceral fat (VF) with hsCRP in non-diabetic adults. METHODSThis was a cross-sectional study performed on 80 non-diabetic adults with ages ranging from 20-40 years. The obesity indices BMI, WC, body fat percentage, and VF were measured. We then measured the hsCRP levels using an immunoturbidimetric method. Simple and multiple linear regression tests were used to analyze the association between obesity indices and hsCRP levels. RESULTSMean of log BMI, log WC, and log VF was 1.41 ± 0.08 kg/m2, 1.93 ± 0.06 cm, and 0.95 ± 0.27 units, respectively. Simple linear regression tests showed that log BMI (â=3.506; p<0.001), log WC (â=3.672; p<0.001), log VF (â=0.833; p<0.001), and log systolic blood pressure (â=3.739; p=0.024) had a significant positive correlation with log hsCRP levels. Further multiple linear regression test showed that log BMI (â=3.772; Beta=0.674; p<0.001) had the greater effect on log hsCRP levels compared to other indices. CONCLUSIONS BMI had a greater influence on hsCRP levels compared to other obesity indices in non-diabetic adults. Body mass index can be used as a better index in predicting hsCRP levels compared to other indices.